KARAKTERISTIK FISIK, KIMIA DAN ORGANOLEPTIK SELAI PADA BERBAGAI RASIO BUAH NAGA MERAH (Hylocereus polyrhizus Britt and Rose) - GULA PASIR - Huriah Huriah; Nur Alam; Abd Hamid Noer (Fakultas Pertanian Universitas Alkhairaat Palu, 2019)
The high water content in dragon fruit causes the fruit to be easily damaged, therefore it needs to be processed to reduce the amount of loss, including making it into jam. In addition, processing dragon fruit into various processed products also aims to overcome the problem of excess production when the harvest season arrives. The aim of this research was to obtain the ratio of dragon-sugar fruit which gave the best influence on the physical, chemical and organoleptic characteristics of jam. The study used a completely randomized design (CRD) for the analysis of physical parameters of jam (softness) and chemical jam (water content, total dissolved solids, anthocyanin and vitamin C levels). Randomized Group Design (RBD) for analysis of organoleptic test parameters (color, texture, taste and preference). As a treatment, it is the ratio of dragon-sugar, which consists of five levels of treatment, namely P1 = dragon fruit 450 g: granulated sugar 550 g, P2 = dragon fruit 500 g: granulated sugar 500 g, P3 = dragon fruit 550 g: sugar 450 g, P4 = dragon fruit 600 g: granulated sugar 400 g, P5 = dragon fruit 650 g: granulated sugar 350 g. Each treatment was repeated 3 times so that there were 15 experimental units. The data obtained were analyzed using F test 0.01 and 0.05. If the treatment has a significant or very real effect, then proceed with the BNJ test at tararf 0.01 and 0.05. The results showed that treatment P4 (600: 400 b / b dragon-sugar ratio) gave the best influence on the physical, chemical and organoleptic characteristics of dragon fruit jam. This treatment can reduce the use of sugar by 15 percent from the standard use of sugar in making jam.